2021
DOI: 10.3389/fpls.2021.656144
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate NH4+/NO3– Ratio Triggers Plant Growth and Nutrient Uptake of Flowering Chinese Cabbage by Optimizing the pH Value of Nutrient Solution

Abstract: Compared with sole nitrogen (N), the nutrition mixture of ammonium (NH4+) and nitrate (NO3–) is known to better improve crop yield and quality. However, the mechanism underlying this improvement remains unclear. In the present study, we analyzed the changes in nutrient solution composition, content of different N forms in plant tissues and exudates, and expression of plasma membrane (PM) H+-ATPase genes (HAs) under different NH4+/NO3– ratios (0/100, 10/90, 25/75, 50/50 as control, T1, T2, and T3) in flowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“…In this study, the total N content of the three treatments (T1, T2, and T3) was significantly increased at 0-15 d after treatment compared to that of the control treatment with NO 3 − alone (Figure 3A). This is consistent with previous studies on Chinese flowering cabbage [13]. Total N accumulation increased continuously throughout the growth period of the Chinese kale.…”
Section: N Content and N Use Efficiencysupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, the total N content of the three treatments (T1, T2, and T3) was significantly increased at 0-15 d after treatment compared to that of the control treatment with NO 3 − alone (Figure 3A). This is consistent with previous studies on Chinese flowering cabbage [13]. Total N accumulation increased continuously throughout the growth period of the Chinese kale.…”
Section: N Content and N Use Efficiencysupporting
confidence: 93%
“…A plant's uptake of different forms of N and its transport and assimilation mechanisms depend on its NH 4 + /NO 3 − ratios. Our recent research further showed that an appropriate NH 4 + /NO 3 − ratio triggers plant growth and nutrient uptake of flowering Chinese cabbage by optimizing pH value in nutrient solution [13].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Studies have shown that the simultaneous application of NH 4 + -N and NO 3 − -N can alleviate toxicity [19]. It is easier for plants to adjust their intracellular pH and store a portion of N through a small amount of energy to obtain higher yields and economic effects [20,21].…”
Section: Introductionmentioning
confidence: 99%